Maximum and Minimum Energy in Vortex Motion - Elzebair, Amna Mohammed Osman (Journal of natural sciences, life and applied sciences, 2017)
This paper is discussion the Maximum and minimum energy in vortex motion exploited the conservation of vorticity as well as energy in two-dimensional motion of an incompressible inviscid fluid, to find some quite general criteria for stability of steady basic flows, and also steady Bènard convection sets in at the critical value of the Rayleigh number. This paper also discussion some experiments with a silicone oil (of Prandtl number100). (Abstract text Times New Roman, size 12, italic. Spacing-SINGLE). These guidelines provide instructions to format your paper. Please write directly into the template or copy your finished text into it choosing ‘match destination formatting’. Please use the predefined formatting styles instead of applying your individual settings. The paper shall be written in compliance with these instructions. Please review this document to learn about the formatting of text, table captions and references. The conference proceedings will be published in an electronic format. The Abstract should be no more than 200 words and one paragraph only. Avoid quotation and citing references in your abstract.
Keywords: Landau constant; Nusselt number; Prandtl number; Rayleigh number; Reynolds number